Constitutive Expression of Untranslatable Versions of the p25 Coat Protein Gene of Citrus tristeza virus (CTV) in Transgenic Mexican Lime Plants Does Not Confer Resistance to the Virus - Domínguez, A.; Fagoaga, Carmen; Navarro, Luis; Moreno, Pedro; Pena, Leandro (IOCV, 2021)
To develop RNA-mediated resistance (RMR) against Citrus tristeza virus (CTV), Mexican lime plants were transformed with two modified versions of CTV p25 gene: I) the complete p25 ORF derived from the severe strain T305, mutated to make its mRNA untranslatable, and II) an untranslatable fragment of the p25 gene fused to the green fluorescent protein (gfp) gene. Forty-eight independent transgenic lines were obtained in total, and Southern blot analyses revealed that all incorporated the corresponding p25 sequence. Some of them showed post-transcriptional gene silencing (PTGS) of the p25 transgene, which has been associated to RMR in other transgenic plant-virus interactions. After graft-inoculation with the homologous CTV strain, transgenic plants developed symptoms and virus accumulated at similar rates than in non-transgenic control plants. Factors potentially involved in this protection failure are discussed.